Risk factors for sustained virological non-suppression among children and adolescents living with HIV in Zimbabwe and Malawi: a secondary data analysis - Christi Jackson; Andrea M. Rehman; Grace McHugh; Carmen Gonzalez-Martinez; Lucky G. Ngwira; Tsitsi Bandason; Hilda Mujuru; Jon O. Odland; Elizabeth L. Corbett; Rashida A. Ferrand; Victoria Simms (BMC Pediatrics, 2022)
Abstract Background We investigated risk factors for sustained virological non-suppression (viral load ≥ 1000 copies/ml on two tests 48 weeks apart) among children and adolescents accessing HIV care in public sector clinics in Harare, Zimbabwe and Blantyre, Malawi. Methods Participants were enrolled between 2016 and 2019, were aged 6–19 years, living with HIV, had chronic lung disease (FEV z-score < -1) and had taken antiretroviral therapy (ART) for at least six months. We used multivariate logistic regression to identify risk factors for virological non-suppression after 48 weeks, among participants who were non-suppressed at enrolment. Results At enrolment 258 participants (64.6%) were on first-line ART and 152/347 (43.8%) had virological non-suppression. After 48 weeks 114/313 (36.4%) were non-suppressed. Participants non-suppressed at baseline had almost ten times higher odds of non-suppression at follow-up (OR = 9.9, 95%CI 5.3–18.4, p < 0.001). Of those who were non-suppressed at enrolment, 87/136 (64.0%) were still non-suppressed at 48 weeks. Among this group non-suppression at 48 weeks was associated with not switching ART regimen (adjusted OR = 5.55; 95%CI 1.41–21.83); p = 0.014) and with older age. Twelve participants switched regimen in Zimbabwe and none in Malawi. Conclusions Viral non-suppression was high among this group and many with high viral load were not switched to a new regimen, resulting in continued non-suppression after 48 weeks. Further research could determine whether improved adherence counselling and training clinicians on regimen switches can improve viral suppression rates in this population. Trial registration Secondary cohort analysis of data from BREATHE trial (Clinicaltrials.gov NCT02426112 ).